Dating app users after two years: A Dark Triad amplification - Freyth, Lennart (Studia Psychologica: Theoria et praxis, 2022)
A 2-year longitudinal study examined how dating app use (N = 82, 36 women) affects changes in personality (i.e., the Dark Triad and Big Five traits), and visual social media use (i.e., dating apps, Instagram). Dating app users were higher in narcissism and Machiavellianism after two years but not in the Big Five traits. Early time and sessions on dating apps were associated with more sessions on dating apps, more time on Instagram, and higher narcissism later. Men increased in narcissism, women decreased in extraversion, openness, conscientiousness, and increased in agreeableness. The use of dating apps affects personality into an antagonistic direction, especially women.